Biochemical and spectroscopic characterization of photocomplexes from the extremely halophilic purple sulfur bacterium, Halorhodospira halophila strain SL1T - I. Satoh; K. Inada; N. Hiwatashi; S. Ohara; N. Shimazaki; E.R. Purba; T. Mochizuki; A. Mizoguchi; L.-J. Yu; J. Overmann; M.T. Madigan; K. Tani; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2026)

The Kellwasser events in the Upper Devonian Frasnian to Famennian transition in the Toc Tat Formation, northern Vietnam - Toshifumi Komatsu; Ryota Urakawa; Toshitaka Inada; Kazuki Yamauchi; Takumi Maekawa; Reishi Takashima; Mark Williams; Phong D. Nguyen; Hung D. Doan; Minh T. Nguyen; Shuji Niko; Gengo Tanaka; et al. (Island Arc, 2019)
Upper Devonian carbonates of the Toc Tat Formation in the Si Phai Pass area of Dong Van District, northern Vietnam were deposited in carbonate platform, slope, and basin environments. These carbonates yield abundant conodonts indicative of the Palmatolepis nasuta , Pa. linguiformis and Pa. triangularis zones, the Frasnian–Famennian stage boundary being identified by the first occurrence of Pa. triangularis . Two positive carbon isotope excursions are recognized, the lower excursion peaking in the interval of the lower to middle Pa. nasuta Zone, whilst the upper excursion peaks just above the local Frasnian–Famennian boundary. Based on the biostratigraphy, these excursions equate to the Lower and Upper Kellwasser events. Locally, tentaculitoid taxa ( Nowakia , Styliolina , Homoctenus, and Metastyliolina ?) are abundant in the interval of the Pa. nasuta Zone, but show a drastic decline in abundance before the Lower Kellwasser Event, and only two taxa survived into the Famennian.

Development of simple, rapid and sensitive detection assay for grouper nervous necrosis virus using real‐time loop‐mediated isothermal amplification - T Mekata; J Satoh; M Inada; S Dinesh; P Harsha; T Itami; R Sudhakaran (Journal of Fish Diseases, 2015)
A quantitative rapid detection method based on loop‐mediated isothermal amplification has been developed for red‐spotted grouper nervous necrosis virus ( RGNNV ). The nested polymerase chain reaction ( PCR ) assay is the mainstream inspection of the brooder in the hatchery. In this study, a real‐time loop‐mediated isothermal amplification ( LAMP ) method has been applied for RGNNV detection, known as a high‐speed gene amplification procedure. Of the three temperatures (60 °C, 63 °C and 65 °C) attempted, it has been found that 63 °C is giving higher amplification from 11th minute onwards. Sensitivity analysis performed in comparison with real‐time polymerase chain reaction, reverse transcriptase PCR and nested RT ‐ PCR using various concentrations of template revealed that real‐time LAMP method is efficient in terms of cost and time consumption. Specificity analysis revealed that the method developed is specific to RGNNV , whereas it has sequence cross‐match with tiger puffer NNV giving advantage in detecting both the viruses. This method could be much efficient in analysing RGNNV in combination with TPNNV .

Dedifferentiation of starch-storing cultured tobacco cells: effects of 2,4-dichlorophenoxy acetic acid on multiplication, starch content, organellar DNA content, and starch synthesis gene expression - Y. Miyazawa; N. Kutsuna; N. Inada; H. Kuroiwa; T. Kuroiwa; S. Yoshida (Plant Cell Reports, 2002)

Senescence in the nongreening region of the rice (Oryza sativa) coleoptile - N. Inada; A. Sakai; H. Kuroiwa; T. Kuroiwa (Protoplasma, 2000)

Senescence program in rice (Oryza sautiva L.) leaves: Analysis of the blade of the second leaf at the tissue and cellular levels - N. Inada; A. Sakai; H. Kuroiwa; T. Kuroiwa (Protoplasma, 1999)

Predation on Euphausia pacifica by demersal fishes: predation impact and influence of physical variability - O. Yamamura; T. Inada; K. Shimazaki (Marine Biology, 1998)

Cats are protected against feline immunodeficiency virus infection following vaccination with a homologous AP-1 binding site-deleted mutant - M. Kohmoto; T. Miyazawa; E. Sato; K. Uetsuka; Y. Nishimura; Y. Ikeda; G. Inada; K. Doi; T. Mikami (Archives of Virology, 1998)

Phylogenetic analysis of feline immunodeficiency virus isolated from cats in Taiwan - G. Inada; T. Miyazawa; Y. Inoshima; M. Kohmoto; Y. Ikeda; C. -H. Liu; J. A. Lin; T. -F. Kou; T. Mikami (Archives of Virology, 1997)

Genetic basis for Ia positivity and susceptibility to lactic dehydrogenase virus in macrophages of SJL/J mice - T. Inada; C. A. Mims (Archives of Virology, 1987)

Pattern of infection and selective loss of Ia positive cells in suckling and adult mice inoculated with lactic dehydrogenase virus - T. Inada; C. A. Mims (Archives of Virology, 1985)